(untitled) (Bangladesh Medical Journal Khulna, 2016)
The congenital idiopathic clubfoot (CICF) is one of the most common serious birth defect of human bones and joints. Deformity leads to downward spiral of disability, dependency and demoralization. The Ponseti technique has become the standard for treatment of congenital clubfoot in the last 2 decades and a triumph in the very complex field of management of congenital idiopathic clubfoot. In this clinical study, our main aim is to evaluate necessity of the Ponseti treatment protocol in a timely, safe, effective & sustainable manner. In this clinical trial, 621 patients (with a total 1033 feet) of 00 (from birth) to 36 months of age were selected as the study population since October, 2009. Most of them were male children (71.3%) and majority were in >03-06 months of age group. In most of the patients (about 92%), only 05 serial plasters were found to be effective & quite sufficient, whereas, only in 5.3% patients, 06-07 plasters were required followed by 1.7% patients requiring more than 07 plasters. In this study, 06 resistant cases were found where correction was relatively slower than others, but no case of treatment failure was identified. The Mid foot score (MS) found to fall greatly in plaster phases and at the end of 5h plaster it was significantly lower (0.2), whereas, in case of the Hind foot score (HS), it declined rapidly following the percutaneous tenotomy (0.2) Then the total score (TS) trends to fall to near 0, at the end of 3rd post SFAB (Steenbeek Foot Abduction Brace) routine follow up and is maintained thereafter. Approximately 74. 1% patients ultimately required tenotomy of Tendo Achilles as a part of management and the rate was highest (83.6%) in >30-36 months age group, followed by 80.0% in >24-30 months age group. The relapse rate was estimated within post SFAB routine follow up, 1.9% was within 1st 6 months & 2-1% within 6 12 months after removal of bracing. All steps in all patients were done as day case procedures. No cases of posterior-medial release was required, as like the conventional or the original Ponseti treatment protocol, hence found cost effective to the patients with excellent patient’s compliance (P<0.01) Bang Med J (Khulna) 2015; 48 : 11-15